Pelatihan Dan Pendampingan Perajin Bambu Desa Grujugan Untuk Meningkatkan Kualitas Irat Dan Diversifikasi Produk - Siti Khomsah; Novanda Alim Setya Nugraha; Wenny Marlini; Halim Qista Karima; Blandina Hendrawardani (Forum Kerjasama Pendidikan Tinggi, 2023)
Grujugan Village in Kebumen Regency is bamboo craftsmen village. Eighty percent of the population are bamboo craftsmen. The problems faced are the quality of Irat and product diversification. Irat is a thin sheet of bamboo, it is the raw material to make a craft. The thickness of the Irat is not at the same standard because the craftsman thinning material using traditional knife. In other hand, capacity and quickness of production is low because craftsmen do it manually. Meanwhile, product variations are still in a few kinds, such as bamboo’s hat (tudung), several type of food container, and hand-held-fan. Therefore, this community service aims to provide workshops and mentoring on the diversification of existing crafts and manufacture of better bamboo materials using machines. To do this, the community service team will be training how to making cups from bamboo and also how to thinning using the bamboo’s slicing machines. These activities took place form Juli until October in Grujugan Village. Based on the effort, The quality and thickness of the fibers is getting better and uniform. The use of machines can increase the capacity and rate production of Irat, from 1280 to15360 pieces per 8 hours. And also, craftsmen already have the capability to make new products, namely bamboo cup, although the quality is not yet fit for standard market.